An Exploratory Study Combining Eye-Tracking and Virtual Reality: Are Pulses Good “Eye-Catchers” in Virtual Supermarket Shelves? - Melendrez-Ruiz, Juliana; Goisbault, Isabelle; Charrier, Jean-Christophe; Pagnat, Kevin; Dujourdy, Laurence; Arvisenet, Gaëlle; Chambaron, Stéphanie (Frontiers in Virtual Reality, 2021)
Despite numerous health and environmental benefits, the consumption of pulses (i.e. lentils, chickpeas…) in France has decreased over the past few decades. One potential barrier to pulse consumption may be their shelf placement in French supermarkets. We studied gaze behavior toward pulses in a virtual supermarket. Products from four food categories (animal-based, pulses, starches, and vegetables) were randomly presented on 4 shelves (canned, dried, ready-to-eat, and refrigerated). Then, a composite super-shelf combined the canned, dried, and refrigerated shelves. Gaze behavior was recorded for the 108 participants in two screening phases: (i) the four shelves one-by-one, (ii) the super-shelf. Pulses were not strong “eye-catchers”: gaze behavior toward pulses varied from shelf to shelf. Similarly, visual attention was different for each food-group during super-shelf screening. These results could be used to implement specific strategies that should be developed in supermarkets to encourage the choice of pulses by consumers, and thus increase pulse consumption.